Al‐Rich AlGaN Channel High Electron Mobility Transistors on Silicon: A Relevant Approach for High Temperature Stability of Electron Mobility - Julien Bassaler; Jash Mehta; Idriss Abid; Leszek Konczewicz; Sandrine Juillaguet; Sylvie Contreras; Stéphanie Rennesson; Sebastian Tamariz; Maud Nemoz; Fabrice Semond; Julien Pernot; Farid Medjdoub; et al. (Advanced Electronic Materials)
Abstract Ultrawide bandgap (UWBG) semiconductors offer new possibilities to develop power electronics. High voltage operation for the off‐state as well as high temperature stability of the devices in on‐state are required. More than AlGaN/GaN heterostructures, AlGaN/AlGaN heterostructures are promising candidates to meet these criteria. Furthermore, the possibility to choose the Al molar fraction of AlGaN paves the way to more tunable heterostructures. In this study, the electronic transport properties of AlGaN channel heterostructures grown on silicon substrates with various aluminum contents, focusing on the temperature dependence of the electron mobility, is investigated. Experimental results from Hall effect measurements are confronted with carrier scattering models and deep level transient spectroscopy analysis to quantify limiting effects. These results demonstrated the significant potential of Al‐rich AlGaN channel heterostructures grown on silicon substrates for high power and high temperature applications.